Effects of ivermectin and midecamycin on ryanodine receptors and the Ca(2+)-ATPase in sarcoplasmic reticulum of rabbit and rat skeletal muscle - Ahern, Gerard P (Blackwell Science Inc, 1999)
1. Ryanodine receptor (RyR) Ca(2+) channels in the sarcoplasmic reticulum (SR) of skeletal muscle are regulated by the 12 kDa FK506- (or rapamycin-) binding protein (FKBP12). Rapamycin can also activate RyR channels with FKBP12 removed, suggesting that compounds with macrocyclic lactone ring structures can directly activate RyRs. Here we tested this hypothesis using two other macrocyclic lactone compounds, ivermectin and midecamycin. 2. Rabbit skeletal RyRs were examined in lipid bilayers. Ivermectin (cis, 0.66–40 μm) activated six of eight native, four of four control-incubated and eleven of eleven FKBP12-‘stripped’ RyR channels. Midecamycin (cis, 10–30 μm) activated three of four single native channels, six of eight control-incubated channels and six of seven FKBP12-stripped channels. Activity declined when either drug was washed out. 3. Neither ivermectin nor midecamycin removed FKBP12 from RyRs. Western blots of terminal cisternae (TC), incubated for 15 min at 37 °C with 40 μm ivermectin or midecamycin, showed normal amounts of FKBP12. In contrast, no FKBP12 was detected after incubation with 40 μm rapamycin. 4. Ivermectin reduced Ca(2+) uptake by the SR Ca(2+)-Mg(2+)-ATPase. Ca(2+) uptake by TC fell to ∼40% in the presence of ivermectin (10 μm), both with and without 10 μm Ruthenium Red. Ca(2+) uptake by longitudinal SR also fell to ∼40% with 10 μm ivermectin. Midecamycin (10 μm) reduced Ca(2+) uptake by TC vesicles to ∼76% without Ruthenium Red and to ∼90% with Ruthenium Red. 5. The rate of rise of extravesicular [Ca(2+)] increased ∼2-fold when 10 μm ivermectin was added to TC vesicles that had been partially loaded with Ca(2+) and then Ca(2+) uptake blocked by 200 nm thapsigargin. Ivermectin also potentiated caffeine-induced Ca(2+) release to ∼140% of control. These increases in Ca(2+) release were not seen with midecamycin. 6. Ivermectin, but not midecamycin, reversibly reduced Ca(2+) loading in four of six skinned rat extensor digitorum longus (EDL) fibres to ∼90%, and reversibly increased submaximal caffeine-induced contraction in five of eight fibres by ∼110% of control. Neither ivermectin nor midecamycin altered twitch or tetanic tension in intact EDL muscle fibres within 20 min of drug addition. 7. The results confirm the hypothesis that compounds with a macrocyclic lactone ring structure can directly activate RyRs. Unexpectedly, ivermectin also reduced Ca(2+) uptake into the SR. These effects of ivermectin on SR Ca(2+) handling may explain some effects of the macrolide drugs on mammals.